2015
DOI: 10.3109/13561820.2015.1021002
|View full text |Cite
|
Sign up to set email alerts
|

The use of information and communications technologies in the delivery of interprofessional education: A review of evaluation outcome levels

Abstract: Interprofessional education (IPE) in health and human services educational and clinical settings has proliferated internationally. The use of information and communication technologies (ICTs) in the facilitation of interprofessional learning is also growing, yet reviews of the effectiveness of ICTs in the delivery of pre- and/or post-licensure IPE have been limited. The current study's purpose was to review the evaluation outcomes of IPE initiatives delivered using ICTs. Relevant electronic databases and journ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 60 publications
0
37
0
Order By: Relevance
“…This experience was typified by positive factors but also highlighted challenges of facilitation, particularly in the synchronous environment. Both positive factors and challenges have similarly been reported as part of the student's online IPE experience (Curran et al 2015) and for facilitators in other online learning environments (e.g. Cornelius 2014).…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…This experience was typified by positive factors but also highlighted challenges of facilitation, particularly in the synchronous environment. Both positive factors and challenges have similarly been reported as part of the student's online IPE experience (Curran et al 2015) and for facilitators in other online learning environments (e.g. Cornelius 2014).…”
Section: Discussionmentioning
confidence: 83%
“…While accounts of online IPE are increasingly reported in the literature (e.g. Curran et al 2015), this review identified only 10 studies that discussed online IPE facilitation in some depth. These studies provide some insights into a range of aspects of online IPE facilitation, however this limited number clearly highlights the need for further exploration of this expanding area of health professions education.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations